Adipose tissue dysfunction in obese horses with equine metabolic syndrome. (10th April 2019) - Reynolds, A.; Keen, J. A.; Fordham, T.; Morgan, R. A.
Summary: Background: Obesity is a common feature of equine metabolic syndrome (EMS). In other species, obese adipose tissue shows pathological features such as adipocyte hypertrophy, fibrosis, inflammation and impaired insulin signalling all of which contribute to whole body insulin dysregulation. Such adipose tissue dysfunction has not been investigated in horses. Objectives: To determine if obese horses with EMS have adipose tissue dysfunction characterised by adipocyte hypertrophy, fibrosis, inflammation and altered insulin signalling. Study design: Cross‐sectional post‐mortem study. Methods: Samples of peri‐renal (visceral) and retroperitoneal adipose tissue were obtained at post‐mortem from healthy horses (n = 9) and horses with EMS (n = 6). Samples were analysed to determine average adipocyte size, fibrotic content and expression of inflammatory and insulin signalling genes. Results: Horses with metabolic syndrome showed marked adipocyte hypertrophy and increased expression of adipokines (leptin) and inflammatory cytokines ( TNFα, IL1β and CCL2 ) in both adipose tissue depots compared to healthy horses. There were no differences in fibrosis or expression of genes relating to insulin signalling between the groups. Main limitations: Cases used in this study had advanced EMS and may represent the end stage of the condition; the design of the study is such that we were unable to relate the identified adipose tissue dysfunction to whole body insulin dysregulation. Conclusions: Horses with obesity and EMS have significant dysfunction of the peri‐renal and retroperitoneal adipose tissue that may contribute to whole body insulin dysregulation.